Analisis Kemampuan Penalaran Matematis Siswa dalam Menyelesaikan Soal Materi Dimensi Tiga - Gustiadi, Ardi; Agustyaningrum, Nina; Hanggara, Yudhi (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2021)
The purpose of this study was to describe students' mathematical reasoning abilities in solving three-dimensional material problems. The measured mathematical reasoning ability indicators include presenting mathematical statements in written and pictured (I1), submitting conjectures (I2), manipulating mathematics (I3), compiling evidence, giving reasons for the truth of the solution (I4), and making conclusions (I5). This research was a descriptive qualitative research with the subject of research were the students of class XII IPS 2 of SMA Negeri 5 Batam, which number 43 students. Data collection techniques using tests and interviews. The data collected was analyzed by procedures according to Miles and Huberman which included data reduction, data presentation, and concluding. Based on the analysis results, there were 32.5% of the subjects studied had a high mathematical reasoning ability by obtaining an average of 78.11 which needs to be increased again to I5 because it obtained an average with a low category of 47.43%. For moderately capable students there are 27.5% of the subjects studied by obtaining an average of 63.63 but for an average score ofÂ I4 and I5 is 57.77% still needs to be improved and for students with low ability there is 40% from the subjects studied by obtaining an average of 42.08 which needs to be increased again for all indicators of mathematical reasoning ability.